Ocular Trauma with Ophthalmic Artery Injury as a Rare Cause of Subarachnoid Hemorrhage: a Case Report and Review of the Literature - Veldeman, Michael; Ridwan, Hani; Hasan, Dimah; Rieg, Annette; Clusmann, Hans; Schubert, Gerrit Alexander (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Importance Traumatic avulsion of the ophthalmic artery is a rare cause of subarachnoid hemorrhage (SAH). In this case, a relative minor fall with isolated ocular trauma caused bulbar dislocation and rupture of the ophthalmic artery in its intracranial segment resulting in subarachnoid bleeding.Clinical Presentation In a female patient in her 70s, a direct penetrating trauma to the orbit by a door handle resulted in basal SAH with blood dispersion into both Sylvian fissures. Cerebral angiography revealed a blunt-ending stump at the origin of the ophthalmic artery. To provide protection against further bleeding, a flow diverter stent was placed in the internal carotid artery to cover the origin of the ophthalmic artery. After a longer intensive care stay complicated by pneumonia and respiratory insufficiency, the patient made a full recovery. Of all four reported cases (including ours), delayed cerebral ischemia was seen in one patient and hydrocephalus in two patients. These potential complications necessitate close observation and fitting treatment similar to aneurysmal SAH.Conclusion Due to similar physiologic aspects, this type of bleed mimics many aspects of aneurysmal SAH. In this case, we observed no hydrocephalus or the development of delayed cerebral ischemia. This represents, however, the first reported case treated by placement of a flow diverter stent to prevent rebleeding and pseudoaneurysm formation.
Keywords: subarachnoid hemorrhage; ocular trauma; traumatic brain injury; flow diverter stent; ophthalmic artery avulsion